Supervision of The Principal A Site Study At Educational Service At Central Magelang Regency) - Lestariningsih, Tridadi Sarjono (2011)
The objectives of this research are to describe (1) characteristics of managerial supervision; (2) characteristics of academic supervision of the principal at Educational Service at Central Magelang Regency. This research is a qualitative research using ethnography design. This research is conducted at Educational Service, Magelang Regency. The resource persons in this research are the Principal and the head of Educational Service, Magelang Regency. Data collection method uses observation, in-depth interview, and documentation. Data analysis conducted through data reduction, data presentation, and conclusion. Data validity include credibility, transferability, dependability, and conformability. The results of this research show that: (1) Managerial supervision is directed on the preparation of school's vision and mission, school's program supervision, and program of supervision control. Supervision is given by the Educational Service and school's supervisor. The school's vision and mission are prepared based on the principles of normative, academic, relevant, and visionary. The supervision of school's program is constructed by focusing on natural condition of all available resources and the priority of applying the program, it is unique and different between one school to another schools. Controlling of principal supervision program is applied in the form of guidance, school supervision, class supervision, and school monitoring. The principal supervision is controlled by the head of Educational Service of Central Magelang, supervisor, and the leader of school board; (2) the academic supervision conducted through programs are (a) the implementation of training or workshop to the principal; (b) the opportunity to continue study to the advance level as Master degree; (c) the implementation of the Principle Working Group on programmed and will be continued.